Religion as a Social Institution - Advilionienė, Živilė (Sociologija. Mintis ir veiksmas, 2005)
The aim of the article is analyze the characteristics and functions of religion as a social institution in contemporary society. The is built upon the ideas of Durkheim, Weber, Berger and Luckmann, Grigas, Laumenskaitė. A special attention is given to the concpetions of the social construction of reality and symbolic universe of Berger and Luckmann.
Keywords: religion; social instution; É. Durkheim; M. Weber; P. L. Berger; Th. Luckmann; R. Grigas; I. E. Laumenskaitė